Let's Meet at the Mobile - Learning Dialogs with a Video Conferencing Software for Mobile Devices - Hans L. Cycon and Thomas Schmidt and Gabriel Hege and Matthias Wählisch and Mark Palkow (Kassel University Press, 2008)
Mobile phones and related gadgets in networks are omnipresent at our students, advertising itself as the platform for mobile, pervasive learning. Currently, these devices rapidly open and enhance, being soon able to serve as a major platform for rich, open multimedia applications and communication. In this report we introduce a video conferencing software, which seamlessly integrates mobile with stationary users into fully distributed multi-party conversations. Following the paradigm of flexible, user-initiated group communication, we present an integrated solution, which scales well for medium-size conferences and accounts for the heterogeneous nature of mobile and stationary participants. This approach allows for a spontaneous, location independent establishment of video dialogs, which is of particular importance in interactive learning scenarios. The work is based on a highly optimized realization of a H.264 codec.